Study Study on photoluminescence properties of porous GaP material - Thuy, Pham Thi; Vuong, Bui Xuan (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1, 2018)
This paper reports on the photoluminescence of porous GaPprepared by electrochemical anodization of (111)-oriented bulk material.Porous and bulk GaP exhibits green and red photoluminescence, respectively when excited by the 355-nm laser. The photoluminescence intensity of porous GaP is much stronger than that of the bulk sample. Temperature-dependent time-resolved photoluminescence shows that the green emission gradually decreases when the temperature increases and the photoluminescence full width at haft maximum (FWHM) slightly narrow with decreasing temperature. These results assigned to the contribution of lattice vibrations. Raman scattering measurement is carried out to confirm the size decreasing of the porous GaP material. Keywords PorousGaP, photoluminescence, time-resolved photoluminescence, electrochemical etching References 1. L. T. Canham, Appl. Phys.Lett. 57, 1046 (1990). 2. K. Grigoras, Jpn. J. Appl. Phys. 39, 378 (2000) 3. H. Koyama, J. Appl. Electrochem. 36, 999 (2006) 4. H. A. Hadi, International Letters of Chemistry, Physics and Astronomy, 17(2), 142-152 (2014). 5. S. Setzu, P. Ferrand, and R. Romestain, Mater.Sci. Eng, 34, 69-70 (2000). 6. S. E. Letant and M. J. Sailor, Adv. Mater, 355, 12 (2000). 7. M. T. Kelly, J. K. M. Chun, and A. B. Bocarsly, Nature, 382, 214 (1996). 8. G. Di Francia, V. La Ferrara, L. Quercia, and G. Faglia, J. Porous Mater, 7, 287 (2000). 9. J. Drott, K. Lindstrom, L. Rosengren, and T. Laurell, J. Micromech. Microeng, 7, 14 (1997). 10. B. P. Azeredo, Y. W. Lin, A. Avagyan, M. Sivaguru, K. Hsu, P. Ferreira, Advanced Functional Materials, 26, 2929-2939 (2016). 11. A. Anedda, A. Serpi, V. A. Karavanskii, I. M. Tiginyanu, and V. M. Ichizli, Appl. Phys.Lett, 67, 3316 (1995). 12. A. I. Belogorokhov, V. A. Karavanskii, A. N. Obraztsov and V. Yu. Timoshenko, JETP Lett. 60, 274 (1994). 13. K. Tomioka, S. Adachi, J. App. Phys, 98, 073511 (2005). 14. M. A. Stevens-Kalceff, I. M. Tiginyanu, S. Langa, H. Foll and H. L. Hartnagel, J. App. Phys, 89,2560 (2001). 15. A. V. Zoteev, P. K. Kashkarov, A. N. Obraztsov and V. Y. Timoshenko, Semiconductors, 30, 775 (1996). 16. A. A. Lebedev, V. Y. Rud and Y. V. Rud, Tech. Phys. Lett, 22, 754 (1996). 17. H. Richter, Z. P. Wang, and L. Ley, Solid State Commum, 39, 625 (1981). 18. L. H. Campbell and P. M.Fauchet, Solid State Commum, 58, 739 (1986). 19. V. V. Ursaki, N. N. Syrbu, S. Albu, V. V. Zalamai, I. M. Tiginyanu, and R. W. Boyd, Semicond. Sci. Technl, 20, 745- 748 (2005) 20. R. W. Tjerkstra, Electrochemical and Solid-State Letters,9 (5), C81-C84 (2006)